The dynamics of religious and cultural situation in the post-revolutionary Egypt - Mona Khalil. (Vestnik MGIMO-Universiteta)
In the present article the issue of transformation of religious situation in Egypt after the 2011 revolution is being analyzed. Throughout centuries religion used to and continues to play tremendous role in the Egyptian society. However at the current transitory period conflict between secularly and religiously oriented forces has intensified. Abolishing the prohibition for religiously marked parties and movements to participate in political life of the country has questioned the future of Egypt as the conflict between secularists and religious conservatives has shifted to the political area.